Implementasi Program Bantuan Sosial Pemerintah Program Keluarga Harapan (PKH) terhadap Keluarga Penerima Manfaat (KPM) di Desa Semarum Kecamatan Durenan Kabupaten Trenggalek - Elsa Amalia Trisnanti; Agus Satmoko Adi (Kajian Moral dan Kewarganegaraan, 2022)
Indonesian Conditional Cash Transfer Programme or Program Keluarga Harapan (PKH) is a conditional social assistance program for poor families in the form of cash allocated according to the components in the Beneficiary Families or Keluarga Penerima Manfaat (KPM). In Semarum Village, the PKH program has excited since 2013, but the PKH program is considered unsatisfactory because the number of KPM has not decreased significantly and in practice there are also several obstacle. Therefore, it is important to know the implementation of the PKH program. This research uses the theory of the Edward III public policy implementation model, where there are four factors or variables that influence the success or failure of policy implementation, namely : communication, resources, disposition and bureaucratic structure. The purpose of this research is to understand the implementation of the PKH program and change in KPM conditions before and after the PKH program in Semarum Village, Durenan District, Trenggalek Regency in 2020. The method used in this study is a qualitative approach with a descriptive research design. Selection of informants using purposive sampling technique. Data collection technique using participant observation technique and in-depth interviews. As well as data analysis technique using Huberman and Miles interactive analysis model. The result showed that the implementation of the PKH program on KPM in Semarum Village was successful because of the four factors or variables that affect the success or failure of policy implementation, all of them were achieved. Regarding change in the condition of KPM in Semarum Village before and after the PKH program in 2020, it can be seen from several indication, namely social conditions, economic, education, health and success in breaking the poverty chain.Keywords: implementation, PKH, poverty.